2019
DOI: 10.1007/s00228-019-02645-w
|View full text |Cite
|
Sign up to set email alerts
|

Use of statins in the elderly according to age and indication—a cross-sectional population-based register study

Abstract: Purpose To investigate statin use in the elderly by age (≥ 80 vs. 65-79 years) in relation to established indications. Methods A population-based cohort, including data from four registers, encompassing inhabitants in Region Västra Götaland, Sweden, was used. Statin users were defined as those filling statin prescriptions ≥ 75% of the year 2010. Primary care and hospital diagnoses in 2005-2010 regarding ischemic heart disease, stroke, transient ischemic attacks, and diabetes were considered established indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Furthermore, almost nine in ten of these patients had an underlying established indication for statin treatment. These results are in line with our previous study, where old age was positively associated with the presence of an established indication, suggesting that this age group is more often prescribed statins for secondary prevention [10].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Furthermore, almost nine in ten of these patients had an underlying established indication for statin treatment. These results are in line with our previous study, where old age was positively associated with the presence of an established indication, suggesting that this age group is more often prescribed statins for secondary prevention [10].…”
Section: Discussionsupporting
confidence: 93%
“…In a previous population-based study on statin use in older people according to age and indication [ 10 ], we found a relatively high prevalence of statin users. That is, 17% of all individuals ≥ 80 years of age were on statins in 2010, compared with 23% in the age group 65–80 years.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…The largest observational study to date including 8307 patients older than 85 years has concluded that statin use was not associated with any benefit in incident stroke or death in these patients (25). Data from clinical practice suggest that the oldest old patients are nevertheless prescribed statin therapy, albeit less frequently (26).…”
Section: Dyslipidaemia Controlmentioning
confidence: 99%
“…& Fastbom, 2008;Lea et al, 2019;Lönnbro & Wallerstedt, 2017;Sjoberg et al, 2011). However, one study found that MDD was associated with a lower probability of statin use, and one found that MDD users were less exposed to drug-drug interactions and long-acting benzodiazepines than patients with ordinary prescribing(Johnell & Fastbom, 2008;Sundvall et al, 2019) …”
mentioning
confidence: 99%